2005
DOI: 10.1590/s0004-282x2005000500028
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral isodense epidural hematoma: case report

Abstract: We present a case of a severe head injuried 23 year-old male patient. The initial CT scan disclosed bilateral epidural hematoma, isodense with the brain, thus being a pitfall in diagnosis. Brief case report, image and literature rewiew are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…This has also been described for extradural hematomas [ 5 8 ]. Other authors have reported a case of an intracerebral hematoma that appeared isodense in a patient with disseminated intravascular coagulation [ 9 ].…”
Section: Discussionmentioning
confidence: 69%
“…This has also been described for extradural hematomas [ 5 8 ]. Other authors have reported a case of an intracerebral hematoma that appeared isodense in a patient with disseminated intravascular coagulation [ 9 ].…”
Section: Discussionmentioning
confidence: 69%
“…Generally, acute epidural hematoma appears hyperdense, biconvex mass lesion on CT scan. 3 But unexpectedly few cases have been reported in neurosurgical literature with acute isodense subdural and epidural hematomas. 4 Different radiological presentation of the same pathology is possibly due to decreased hematocrit level or mixing of CSF (Cerebro-spinal fluid) with blood due to dural laceration.…”
Section: Introductionmentioning
confidence: 99%